(3Sdhc GdeQjOjf hWQjb GdYGQajfs ((3YHO Gddg GdYhV GdCejf CMeO eMeO ZdGe Gddg Hf CMeO CHh Mdjeg s)
(3ChdgG (B:s
(3gPG cJGH Sdhc GdeQjOjf hWQjbI GdYGQajf GdMeO ddg GdPi CMce GdCehQ hbOQgG hbOQ GdCTjGA hOHQgG GdehLhOGJ s
(3BNQgG (B:s
(3hJHjY GdeCehQGJ hGdeSfhfGJ hGdeSJMHGJ hjJQc GdeMQeGJ hGdecQhgGJ hGdTHgGJ abO Je gPG GdcJGH Sdhc GdeQjOjf s
(3GdfSNI HgG MhGTs
(3cJGH dg ebOeg Yf ahGFO GdHf GdWHjI ddEfSGf Ke jJMOK Yf Sdhc GdeQjO hGdabjQ hGdUhai hMbjbI cd efge Ke jhVM UdGM GdOjf haSGOgs
(3eGdcg YHO Gddg GdYhV GdCejf s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs